The Impact of Waste Marble Powder as A Partial Alternative Material for Cement - Andreani, Agustina Sus; Taopan , Henda V. R.; Banunaek , Frengky Seki; Nurkhaliza , Farrah (Jurnal Sains Materi Indonesia, 2024)
Waste marble powder generated from the sawing and the mining activity of marble stone caused environmental problems that harmed human health. This current research aimed to investigate the influence of waste marble powder to substitute cement partially in mortar production. The mortar preparation with the mixture compositions of 0-50% marble powder was investigated for their resistance of compression and their porosity. The characterization was assessed with X-ray Fluorescence (XRF), Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), Fourier Transform Infra-Red (FTIR), and X-ray Diffraction (XRD). The finding of this research revealed that a replacement by up to 10% marble powder obtained an increase in compressive strength after 28 days. A low level of marble powder to replace cement led to a less porous microstructure of the mortars. These confirmed that waste marble powder could be applied to manufacture mortars. In addition, the utilization of waste marble powder as an alternative building material would reduce the damage to the environment.